What is the answer for question 2. b) ?

http://postimg.org/image/scirn1jtt/

### 1 Answer | Add Yours

We will use `m log_yx=log_y(x^m)`

`log_y(x)+log_y(z)=log_y(xz)`

`log_y(x)-log_y(z)=log_y(x/z)`

``

We have given.

`3log_5 a+4log_5 b-2log_5 c`

`log_5a^3+log_5b^4-log_5c^2`

`log_5(a^3b^4)-log_5c^2`

`log_5((a^3b^4)/(c^2))`

b. `3log(2)-(1/3)log(x^2-1)`

`=log(2^3)-log((x^2-1)^(1/3))`

`=log(8/(x^2-1)^(1/3))`

``

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes